2022
DOI: 10.1126/scitranslmed.abl6057
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 RNA causes heterochromatin erosion and is a target for amelioration of senescent phenotypes in progeroid syndromes

Abstract: Constitutive heterochromatin is responsible for genome repression of DNA enriched in repetitive sequences, telomeres, and centromeres. During physiological and pathological premature aging, heterochromatin homeostasis is profoundly compromised. Here, we showed that LINE-1 ( Long Interspersed Nuclear Element-1; L1 ) RNA accumulation was an early event in both typical and atypical human progeroid syndromes. L1 RNA negatively regulated the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 71 publications
0
30
0
1
Order By: Relevance
“…Endogenous LINE‐1 de‐repression occurs in both pathological (Della Valle et al, 2022) and physiologically senescent cells (De Cecco et al, 2019; Simon et al, 2019; Van Meter et al, 2014). In addition to its involvement in replicative senescence, LINE‐1 activation is also observed during stress‐induced senescence (Farkash et al, 2006; Kale et al, 2005) (Stribinskis & Ramos, 2006) (Shi et al, 2021) (Lucchinetti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous LINE‐1 de‐repression occurs in both pathological (Della Valle et al, 2022) and physiologically senescent cells (De Cecco et al, 2019; Simon et al, 2019; Van Meter et al, 2014). In addition to its involvement in replicative senescence, LINE‐1 activation is also observed during stress‐induced senescence (Farkash et al, 2006; Kale et al, 2005) (Stribinskis & Ramos, 2006) (Shi et al, 2021) (Lucchinetti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, accumulation of LINE‐1 complementary DNA (cDNA) and widespread expression of the LINE‐1 encoded protein ORF1p in the cytoplasm of deeply senescent cells cause sterile inflammation by activating the type I interferon (IFN‐I) response (De Cecco et al, 2019; Simon et al, 2019). Knockdown of LINE‐1 rescues the progeria phenotype and extends the lifespan of mice (Della Valle et al, 2022). However, the effects of high ambient glucose levels on LINE‐1 activation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests a correlation between aging and the reactivation of specific retroelements, primarily LINEs and HERV-K-derived retrovirus like particles (RVLPs). Prior work has shown that the transcriptional derepression of LINEs in immune cells cells triggers interferon production to contribute to inflammaging ( 7 , 75–77 ). Recent findings have suggested a key role of the endogenous retrovirus HERV-K (HML-2) activation in cellular senescence and tissue aging( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The implications of these findings in the genesis of cancer will be discussed in depth in the next section. Remarkably, a recent study in the context of progeroid syndromes, which are basically caused by lamina defects, has depicted a novel role of LINE-1 RNA transcription in influencing chromatin organization, cell proliferation, DNA damage, and gene expression profiles [ 96 ].…”
Section: Rt Inhibitors Induce Epigenetic Alterations In the Nuclear A...mentioning
confidence: 99%